Twelve-Transmembrane-Segment (TMS) Version (ΔTMS VII-VIII) of the 14-TMS Tet(L) Antibiotic Resistance Protein Retains Monovalent Cation Transport Modes but Lacks Tetracycline Efflux Capacity - Jin, Jie (American Society for Microbiology, 2001)
A “Tet(L)-12” version of Tet(L), a tetracycline efflux protein with 14 transmembrane segments (TMS), was constructed by deletion of two central TMS. Tet(L)-12 catalyzed Na(+)/H(+) antiport and antiport with K(+) as a coupling ion as well as or better than wild-type Tet(L) but exhibited no tetracycline-Me(2+)/H(+) antiport in Escherichia coli vesicles.